Study on the multi-criteria seismic mitigation optimization of a single pylon cable-stayed bridge across strike-slip fault rupture zones. (15th January 2023) - ZENG, Cong; JIANG, Hui; BAI, Xiaoyu; SONG, Guangsong
Highlights: Across-fault ground motions were corrected, decomposed, scaled, and synthesized. Seismic performance of fault-crossing cable-stayed bridge with damper system. Conventional multi-criteria method was improved to optimize fault-crossing angle. Damper system of fault-crossing cable-stayed bridge was optimized. Damping effect of viscous damper system on fault-crossing bridge was investigated. Abstract: Bridge structures across active faults suffer the serious threats from large surface deformation and velocity pulses. This study focuses on developing a multi-criteria optimizing method and investigating the damping effect of the optimized damper system on a cable-stayed bridge across a strike-slip fault. A simplified baseline corrected method is adopted to recover the static offsets in near-fault records and the improved record-decomposition incorporation method is modified to produce artificial across-fault ground motions. A single pylon cable-stayed bridge across a strike-slip fault is taken as the case bridge and the refined nonlinear numerical model is established in OpenSees. The conventional multi-criteria decision making (MCDM) theory is improved by introducing new function forms and a control parameter to assess the best fault-crossing angles of the case bridge. The improved MCDM method is integrated with the beetle antennae search algorithm to optimize the damper system of the case bridge. Finally, the influence of fault-crossing angles and earthquake parameters (permanent displacements and ratios of maximum to permanent displacement) on the damping effect of the optimized damper system are investigated. The results indicate that the cable-stayed bridge reaches optimal seismic performance when the fault-crossing angle is around 90° (75°-105°) as both the biaxial nonlinearity of the pylon and the risk of the girder unseating are reduced. The damper system is efficiently optimized by the proposed method, and the displacement and force demand of the case bridge are balanced. Both the fault-crossing angles and earthquake parameters are observed to have considerable influence on the damping effects. More specifically, the damping effect on most seismic responses is optimized when the fault-crossing angle approaches 90° (60°-120°). As the permanent displacement increases, the damping effect on the pier-girder relative displacement is significantly reduced and the damping effect on the pier moments is moderately decreased. Moreover, the damping effect is improved for all the seismic responses as the ratios of maximum to permanent displacements increase, with the exception of transverse displacement.